2016
DOI: 10.3382/ps/pew033
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparative proteomic study of quail and duck egg white protein using 2-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry analysis

Abstract: A proteomic study of egg white proteins from 2 major poultry species, namely quail (Coturnix coturnix) and duck (Anas platyrhynchos), was performed with comparison to those of chicken (Gallus gallus) through 2-dimensional polyacrylamide gel electrophoresis (2-DE) analysis. By using matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry (MALDI-TOF MS/MS), 29 protein spots representing 10 different kinds of proteins as well as 17 protein spots designating 9 proteins were successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…As a trypsin and chymotrypsin inhibitor, [37] ovoinhibitor has been found in the egg white of chicken, quail, and ostrich. [11] Its deficiency in duck egg white may suggest weaker inhibition of endogenous protease activity and shorter storage period than those of chicken and quail eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a trypsin and chymotrypsin inhibitor, [37] ovoinhibitor has been found in the egg white of chicken, quail, and ostrich. [11] Its deficiency in duck egg white may suggest weaker inhibition of endogenous protease activity and shorter storage period than those of chicken and quail eggs.…”
Section: Resultsmentioning
confidence: 99%
“…As three most consumed avian eggs all over the world, chicken, quail, and duck eggs might have different egg protein patterns due to the adaptation under varied environments and evolution. According to the phylogenetic analysis with whole mitochondrial genome [10] and egg white proteome [11] than duck. These data implied that the protein patterns of these three avian egg yolks were different, which might be of significant importance in biology.…”
Section: Introductionmentioning
confidence: 99%
“…which were able to inhibit serine protease. [2] Hu et al [13] reported that duck ovostatin (ovamacroglobulin) is capable of inhibiting serine protease as well as metalloprotease, while chicken ovostatin inhibits only metalloprotease. Moreover, Shah and Khan [14] proved that duck ovomucoid effectively stabilised salmon calcitonin against hydrolysis mediated by three proteases including trypsin, α-chymotrypsin and elastase.…”
Section: Resultsmentioning
confidence: 99%
“…Protein contents of lyophilised albumen from duck and quail eggs were higher than that of hen egg. [12,13] Moreover, ovomucoid from duck and hen albumen also showed different protease inhibitory activity in protection of salmon calcitonin breakdown by serine proteases. [14] In general, hen albumen has been commonly manufactured into different forms, such as powder, pasteurised liquid albumen, etc.…”
Section: Introductionmentioning
confidence: 99%
“…and, to the best of our knowledge, have rarely been studied and reported [40]. Biological mass spectrometry has been developed as an efficient method for proteomic analysis that exhibits superior mass accuracy and ultra-high resolution, and employs a segmented quadruple mass filter with improved selectivity and ion transmissibility [38,39,41,42,43,44,45,46]. However, for a specific genus, there is only limited data available to characterize the fungal protein.…”
Section: Introductionmentioning
confidence: 99%